Exploring cultural and gender-based variations in emoji interpretation among Malaysian youth - Gan, Gabriel Ee Qi (2025)
The study investigates how culture and gender shape the interpretation and usage of emojis among Malaysian youth. Data was collected through a pre-survey to identify frequently used and ambiguous emojis, along with in-depth interviews with eight participants representing different ethnic and gender groups. The analysis employed Social Semiotics to interpret emojis as semiotic resources situated in cultural and digital practices, alongside Systemic Functional Linguistics (SFL) to examine their ideational, interpersonal, or textual meta-functions. Findings reveal that while certain emojis retain culturally embedded meanings, online culture and digital trends exert a stronger influence on interpretation and usage. Emojis are frequently employed as substitutes for sensitive or taboo topics, with interpretations shaped by global trends, peer influence, and shared social contexts. Gender differences also emerged, with female participants displaying greater caution and sensitivity in emoji use by employing them as politeness markers and face-saving devices more often than their counterparts. This study extends prior research by showing how localized cultural practices persist but increasingly blend with inline subcultural norms. These findings contribute to the understanding of emojis as dynamic meaning-making resources in multicultural digital communication.